Digital Comics as Literacy Learning in Elementary Schools (Current Research in Education: Conference Series Journal, 2024)
The development of technology requires everyone to follow it. The learning process is no exception. In the development of learning, every student must have a high level of literacy. What can help literacy activities and utilize information technology is to do digital literacy activities. Digital literacy can be done without knowing time and place. This makes it easy to access information. Digital comics can be used as one of the media to optimize literacy activities, especially for elementary school students. The purpose of this research is to improve or optimize student literacy, especially in reading literacy in elementary schools. The research method used is descriptive qualitative. The data collection techniques were observation and interview. The results showed that digital comics can improve student literacy in elementary schools. This can be seen based on the results of interviews and observations conducted with teachers and students who stated that digital comic media really attracted students' attention in reading literacy. Students' understanding of reading material becomes more optimal with the combination of digital-based comics.